Within-season distribution of external training and racing workload in professional male road cyclists - Metcalfe, A. J.; Menaspa, P.; Villerius, V.; Quod, M.; Pfeiffer, J. J.; Govus, A. D.; Abbiss, C. R. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To describe the within-season external workloads of professional male road cyclists for optimal training prescription. Methods: Training and racing of 4 international competitive professional male cyclists (age 24 ± 2 y, body mass 77.6 ± 1.5 kg) were monitored for 12 mo before the world team-time-trial championships. Three within-season phases leading up to the team-time-trial world championships on September 20, 2015, were defined as phase 1 (Oct-Jan), phase 2 (Feb-May), and phase 3 (June-Sept). Distance and time were compared between training and racing days and over each of the various phases. Times spent in absolute (<100, 100-300, 400-500, >500 W) and relative (0-1.9, 2.0-4.9, 5.0-7.9, >8 W/kg) power zones were also compared for the whole season and between phases 1-3. Results: Total distance (3859 ± 959 vs 10911 ± 620 km) and time (240.5 ± 37.5 vs 337.5 ± 26 h) were lower (P < .01) in phase 1 than phase 2. Total distance decreased (P < .01) from phase 2 to phase 3 (10911 ± 620 vs 8411 ± 1399 km, respectively). Mean absolute (236 ± 12.1 vs 197 ± 3 W) and relative (3.1 ± 0 vs 2.5 ± 0 W/kg) power output were higher (P < .05) during racing than training, respectively. Conclusion: Volume and intensity differed between training and racing over each of 3 distinct within-season phases.